2021
DOI: 10.1088/1742-6596/1737/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an e-Learning Platform at Graduate School Based on User Experience Evaluation Technique

Abstract: This study was aimed to evaluate the e-learning platform in a graduate school by using User Experience Questionnaire (UEQ). The data were collected from 65 respondents and analyzed using an excel data analysis tool. The results indicate that all six scales of the instrument are consistent except the novelty scale. Also, the calculated means of the scales are slightly positive as all values are greater than 0.8 compared to the UEQ benchmark. Although the respondents show a little positive impression with the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…Various aspects of e-learning platforms' usability need further research via the UEQ (Pandu & Fajar, 2019, Abubakari et al, 2021 to improve teachers' and students' ability to use them. An in-depth assessment of student-teacher interaction through e-learning platforms can be based on Responsive…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of e-learning platforms' usability need further research via the UEQ (Pandu & Fajar, 2019, Abubakari et al, 2021 to improve teachers' and students' ability to use them. An in-depth assessment of student-teacher interaction through e-learning platforms can be based on Responsive…”
Section: Discussionmentioning
confidence: 99%
“…Among his participants, there were students and lecturers of the same online-learning website. The findings indicated that the platform needs some improvements in the user experience aspects [39].…”
Section: User Experience Questionnairementioning
confidence: 99%
“…The application was built to facilitate the relationship between lecturers and students in teaching and learning activities and to follow the development of learning technology. Be-smart was created using the Modular Object-Oriented Dynamic Learning Environment (MOODLE) (Abubakari et al, 2021), a world-famous software package to develop Internet electronic learning media (LPMT Fenomena, 2013).…”
Section: Online Media Usedmentioning
confidence: 99%